Army Warrior Care Project (AWCP): Rationale and methods for a longitudinal study of behavioral health care in Army Warrior Transition Units using Military Health System data, FY2008–2015. Issue 3 (2nd August 2019) - Wooten, Nikki R.; Brittingham, Jordan A.; Hossain, Akhtar; Hopkins, Laura A.; Sumi, Nahid S.; Jeffery, Diana D.; Tavakoli, Abbas S.; Chakraborty, Hrishikesh; Levkoff, Sue E.; Larson, Mary Jo
Abstract: Objectives: Warrior Transition Units (WTUs) are specialized military units co‐located with major military treatment facilities providing a Triad of Care involving primary care physicians, case managers, and military leadership to soldiers needing comprehensive medical care. We describe the rationale and methods for studying behavioral health care in WTUs and characterize soldiers assigned to WTUs. Methods: The Army Warrior Care Project (AWCP) analyzes U.S. Department of Defense Military Health System data to examine behavioral health problems and service utilization among Army soldiers who were assigned to WTUs after returning from Afghanistan and Iraq deployments, FY2008–2015. Results: WTU members ( N  = 31, 094) comprised 3.5% of the AWCP cohort ( N  = 883, 091). Almost all (96.5%) had one WTU assignment for a median of 327 days; 77.3% were assigned before deployment ended, ≤30 or >365 days post‐deployment; 59.4% had deployment‐related behavioral health diagnoses. Conclusions: An overwhelming majority of soldiers had one WTU assignment for almost a year. A substantial proportion of WTU soldiers had psychological impairment, which limited performance of their military duties. The AWCP is the first longitudinal study of redeployed soldiers assigned to WTUs and provides a unique opportunity to advance our understanding of behavioral health among soldiers needing comprehensive medical care after combat deployments.